Gas condensate conversion into high octane gasoline - Rahman, N.A. (Medwell Journals, 2017)
Gasoline production has become a great challenge due to stringent standards enforced. The feasibility of zeolite-based catalyst to be used in the reforming process of gas condensate into high octane gasoline was investigated. Reaction under nitrogen rich gas and hydrogen rich gas were carried out. Characterization of the liquid product was carried out to ensure the local and international standard, MS 118 EURO 2M and EN 228 EURO 5, respectively requirement were fulfilled. © Medwell Journals, 2017.